Silicone breast prosthesis explant: breast reconstruction using the crossed flap technique - Ognev Meireles Cosac; Tristão Maurício de Aquino; José Carlos Daher; Marcela Santos Vilela; Diogo Borges Pedroso (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: In 1963 Cronin and Gerow introduced the use of the silicone implant and its use increased exponentially. However, complications related to implants emerged over time. The set of adverse situations to the use of silicone implants fueled by the growth of social media culminated in an increase in the permanent removal of the implant. Many cases of explants have the inferior pedicle compromised by injury to the perforating vessels, and the crossed flap technique is an alternative for the reconstruction of explanted breasts. Methods: Silicone explants were performed with immediate breast reconstruction without the use of a new implant, motivated by medical indication or the patients own desire. The crossed flap technique was used in all cases. It uses the crossing of parenchymal patches of the superior pedicle, one medial and one lateral, as described by Sperli. Results: 10 cases were operated from 2004 to 2021. The time of use of the prostheses ranged from 3 to 19 years and the main motivation for the explant was capsular contracture. No cases of necrosis were observed. Conclusions: The crossed flap technique is a useful and safe alternative for breast reconstruction surgeries after definitive explantation.